2021
DOI: 10.3390/microorganisms9081736
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Martelella soudanensis sp. nov., Isolated from a Mine Sediment

Abstract: Gram-stain-negative, strictly aerobic, non-spore-forming, non-motile, and rod-shaped bacterial strains, designated NC18T and NC20, were isolated from the sediment near-vertical borehole effluent originating 714 m below the subsurface located in the Soudan Iron Mine in Minnesota, USA. The 16S rRNA gene sequence showed that strains NC18T and NC20 grouped with members of the genus Martelella, including M. mediterranea DSM 17316T and M. limonii YC7034T. The genome sizes and G + C content of both NC18T and NC20 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 53 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…The 16S rRNA gene sequences of M. soudanensis NC18 T and NC20 showed 100% similarity. Comparative 16S rRNA gene sequence analyses revealed that M. soudanensis NC18 T and NC20 were most closely related to M. mediterranea DSM 17316 T (99.0%), Martelella limonii YC7034 T (98.6%), M. endophytica YC6887 T (98.1%), Martelella mangrovi BM9-1 T (97.9%), M. lutilitoris GH2-6 T (97.9%), Martelella radicis BM5-7 T (97.6%), Martelella suaedae YC7033 T (97.6%), and M. caricis GH2-8 T (97.2%) [ 16 ]. The neighbor-joining, maximum-likelihood, and maximum-parsimony phylogenetic analyses revealed that the two isolates formed a lineage within the clade of the genus Martelella but are separate from the clade constituted of the species M. mediterranea and M. limonii ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 16S rRNA gene sequences of M. soudanensis NC18 T and NC20 showed 100% similarity. Comparative 16S rRNA gene sequence analyses revealed that M. soudanensis NC18 T and NC20 were most closely related to M. mediterranea DSM 17316 T (99.0%), Martelella limonii YC7034 T (98.6%), M. endophytica YC6887 T (98.1%), Martelella mangrovi BM9-1 T (97.9%), M. lutilitoris GH2-6 T (97.9%), Martelella radicis BM5-7 T (97.6%), Martelella suaedae YC7033 T (97.6%), and M. caricis GH2-8 T (97.2%) [ 16 ]. The neighbor-joining, maximum-likelihood, and maximum-parsimony phylogenetic analyses revealed that the two isolates formed a lineage within the clade of the genus Martelella but are separate from the clade constituted of the species M. mediterranea and M. limonii ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…1 , S1 ). The ANI and dDDH values between strains NC18 T and NC20 were 99.9% and 100%, respectively [ 16 ]. These results revealed that the two strains belonged to a single species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations